Environmental Education: A strategy to environmentalize the universitary curricula (Biocenosis, 2012)
Interuniversity Commission for Environmental Education (CIEA) of the National Council of Rectors (CONARE), in order to establish its mission, conceived the Environmental Education (EE) as a process to promote awareness, build knowledge, values, attitudes and skills to the positive environmental action. Thus, the EE as a dimension allowing permeate the university curriculum and promote mainstreaming environmental axis. For this, has implemented a training strategy based on the EE as a process, action research and course development. In recent years, these activities have been conducted in the Virtual Learning Community Environment (VLCE) prepared by the CIEA in a research project conducted from 2007 to 2008. The experiences generated in the VLCE processes have led to reflection, awareness and awareness of participatory and responsible environmental action and proposed design courses and projects, both existing and new, looking to incorporate the DA in the university work. This space also allows the accompaniment to feed back the approach of these proposals, which will affect the development of actions to achieve curriculum greening.
Keywords: Action research; Mainstream; Environmental dimension